2011
DOI: 10.1213/ane.0b013e3182043049
|View full text |Cite
|
Sign up to set email alerts
|

Surgeons' and Anesthesiologists' Perceptions of Turnover Times

Abstract: Managers should not rely on surgeons or anesthesiologists for their expert judgment on turnover times. Managers should also not interpret comments about turnover times as literally referring to the time, but instead as factors perceived as contributing to the time (e.g., attitude about the facility and the activity of its personnel).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…9 Despite evidence that these individuals hold much of the responsibility for procedural efficiency, Masursky et al previously found that surgeons were biased when it came to planning OR turnaround times. 11,13 Correcting discrepancies between planned and actual OR turnaround times can reduce patient wait times, potentially enabling more procedures to be performed in a single OR, especially when numerous short surgeries are scheduled. The findings of the current study have potential managerial applications at the Marienhospital in order to increase the accuracy of OR planning and measure OR efficiency; in addition, these results can be used as a yardstick against which future data can be benchmarked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Despite evidence that these individuals hold much of the responsibility for procedural efficiency, Masursky et al previously found that surgeons were biased when it came to planning OR turnaround times. 11,13 Correcting discrepancies between planned and actual OR turnaround times can reduce patient wait times, potentially enabling more procedures to be performed in a single OR, especially when numerous short surgeries are scheduled. The findings of the current study have potential managerial applications at the Marienhospital in order to increase the accuracy of OR planning and measure OR efficiency; in addition, these results can be used as a yardstick against which future data can be benchmarked.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, Masursky et al observed that both surgeons and, to a lesser extent, anaesthesiologists, judged OR turnaround times according to mental models of factors influencing turnover; thus, the perceptions of surgeons or anaesthesiologists should not be relied upon to make OR management decisions. 11 A direct comparison between planned and actual OR turnaround times is useful as any discrepancies between the two times can affect OR efficiency. To this end, the current study aimed to compare factors influencing planned and actual OR turnaround times at a large hospital in Vechta, Northern Germany.…”
mentioning
confidence: 99%
“…We believed that it was important to strictly measure TATs and rigidly define TATs and on-time FCSs. Masursky et al 5 demonstrated that surgeons usually overestimate the amount of time it takes to turn an OR over but that anesthesiologists were overall unbiased. Our data also show that addressing processing issues and personnel performance is effective in increasing OR efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The common perception, especially at academic medical centers, is that prolonged TATs and late FCSs are a necessary part of life. 4,5 A survey conducted by Masursky et al 5 showed that surgeons commonly overestimated TATs irrespective of their operative volume. This finding has led clinical and administrative leadership to set up multidisciplinary committees that focus on improving TATs and on-time FCSs.…”
mentioning
confidence: 99%
“…Häu-fig ist die Wahrnehmung der Wechselzeiten sowie der Gründe für Verzögerungen auch emotional gefärbt und das gefühlte Ausmaß lässt sich aus den dokumentierten Zeiten nicht nachvollziehen [13]. Hier spielt auch die Wertschätzung der Arbeit aller Berufsgruppen eine große Rolle.…”
Section: Kennzahlen Und Berichtswesenunclassified